IMPLEMENTATION OF CIPP MODEL FOR ONLINE LEARNING EVALUATION DURING COVID-19 PANDEMIC - Heni Purwaningsih; Hanandyo Dardjito (Getsempena English Education Journal, 2021)
This study aims to evaluate the (TESOL) English online learning in a private middle-school in Bantul, Yogyakarta, Indonesia using the Context, Input, Process, Product (CIPP) model of Stufflebeam. This qualitative research collected the data using observation, interview, and document analysis. The research results were be analyzed qualitatively by applying discourse analysis. The result of the study implied that in Context, the school had tensions on the students of grade seven and eight in achieving minimum accomplishment criteria and grade nine in acquiring the minimum graduation criteria. The Input indicated that the human resource, syllabus and essential material, and facilities were sufficiently available. The Process disclosed that the teachers had a different approach in virtual teaching. The Product showed the average score of the final semester test for grades seven and eight were under by the minimum accomplishment criteria but grade nine achieved the target.